SARS-CoV-2 spike peptide analysis reveals a highly conserved region that elicits potentially pathogenic autoantibodies: implications to pan-coronavirus vaccine development - Diaz, Marilyn; Mikulski, Zbignew; Leaman, Dan; Gandarilla, Angel; Da Silva, Nathalia; Verkoczy, Annie; Zhang, Jinsong; Verkoczy, Laurent (Frontiers in Immunology, 2025)
The SARS-CoV-2 pandemic, while subsiding, continues to plague the world as new variants emerge. Millions have died, and millions more battle with the debilitating symptoms of a clinical entity known as long Covid. The biggest challenge remains combating an ever-changing variant landscape that threatens immune evasion from vaccine and prior infection-generated immunity. In addition, the sequelae of symptoms associated with long Covid almost certainly point to multiple pathologies that range from direct damage to organs during infection to a potential role for infection-induced autoreactive antibodies in promoting autoimmune-like conditions in these patients. In this study, a peptide scan of the SARS-CoV-2 spike protein was done to detect novel, highly conserved linear epitopes that do not elicit autoantibodies. We identified eight predicted linear epitopes capable of eliciting anti-spike IgG antibodies. Immunizations alternating peptide conjugated to KLH with the full trimer yielded the highest antibody levels, but homologous immunization with some of the peptides also yielded high levels when an additional immunization step was added. Of all regions tested, the stem helix adjacent to the heptad repeat 2 (HR2) region also elicited high levels of autoreactive antibodies to known autoantigens in common systemic autoimmune disorders such as lupus and scleroderma and may contribute to the long Covid syndrome seen in some patients. Implications to vaccine design are discussed.